2012
DOI: 10.1063/1.3673553
|View full text |Cite
|
Sign up to set email alerts
|

Polarity-dependent photoemission spectra of wurtzite-type zinc oxide

Abstract: The polar surfaces of wurtzite-type zinc oxide (ZnO) were characterized by x-ray photoemission spectroscopy to identify the origin of the polarity dependence of the valence band spectra. A characteristic sub-peak always appeared in the valence band spectra of the (0001) face regardless of the surface preparation conditions. It also appeared in the valence band spectra of the (101¯2) face, but only when the photoelectron take-off angle was parallel to the c-axis of ZnO. Our analysis demonstrates that this take-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Therefore, we can conclude that the VB‐XPS is an appropriate method to determine the polarity. Here, we denote two peaks (P 1 and P 2 ), and the intensity ratio between these peaks is regarded as the fingerprint of crystalline polarity . It should be noted that the polarity dependence of the VB‐XPS profile is significant when the VB‐XPS is measured for the (000 l ) surface with normal emission geometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we can conclude that the VB‐XPS is an appropriate method to determine the polarity. Here, we denote two peaks (P 1 and P 2 ), and the intensity ratio between these peaks is regarded as the fingerprint of crystalline polarity . It should be noted that the polarity dependence of the VB‐XPS profile is significant when the VB‐XPS is measured for the (000 l ) surface with normal emission geometry.…”
Section: Resultsmentioning
confidence: 99%
“…After deposition, the electronic structures were characterized using X‐ray photoelectron spectroscopy (XPS) without an exposure to air, using a monochromated Al K α X‐ray source (1486.6 eV) for excitation. All of the XPS measurements were performed with normal emission geometry at room temperature to determine crystalline polarity of the ZnO films through characterizations of spectral features in valence band XPS (VB‐XPS) spectra . Then, the film thickness was determined by a surface profiler and the averaged deposition rate was calculated from the film thickness and deposition time.…”
Section: Methodsmentioning
confidence: 99%
“…Above the gap, 3.34 eV for both films, there was a slightly sharper edge for the O-polar film indicating that it had better crystalline quality than the Zn-polar film. This was not expected as it is usually found that the O-polar films have more defects than the Zn-polar films [4][5][6][7]. Figure 2(a) shows the MCD data for the O-polar and Zn-polar ZnO films of thickness 400 nm grown by MBE on sapphire substrates.…”
Section: Films Of Zno Grown By Mbementioning
confidence: 88%
“…ZnO is a polar material and it is known that there are a number of differences between samples that are grown with an O-polar or a Zn-polar exposed surface. These include the density of structural defects, tendency to absorb impurities and optically active states associated particularly with the O-polar surface [4][5][6][7]. There are many applications of polar films of ZnO in heterojunctions [8], for catalysis [9] and for enhanced piezoelectricity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to determine the polarity of ZnO. Several methods such as conver- gent beam electron diffraction (CBED), etching, coaxial impact collision ion scattering spectroscopy (CAICISS), and X-ray photoelectron spectroscopy (XPS) have been used for determining the polarity of ZnO [3][4][5][6]. Among these methods, CBED and etching are destructive methods.…”
Section: Introductionmentioning
confidence: 99%